Optimalisasi Peningkatan Kinerja Karyawan Melalui Quality of Work Life, Islamic Work Ethics dan Employee Engagement: Studi pada Karayawan RSI Sultan Agung Semarang - Annisa Nur Hasyimiyah; Widiyanto Widiyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines how Islamic work ethics and quality of work life affect employee performance, using Sultan Agung Islamic Hospital in Semarang as a mediating variable. One hundred workers completed questionnaires for the quantitative study, which was then evaluated using the Sobel Test and multiple linear regression. The findings show that Islamic work ethics and quality of work life have a positive impact on employee engagement and performance, while employee engagement has a positive impact on performance but has not been able to mediate the relationship between the two variables and performance. It follows that balancing technical, spiritual, and work-life factors is necessary to improve performance. It is anticipated that Sultan Agung Islamic Hospital would keep enhancing the standard of living and Islamic principles. For more general findings, more study with more variables and a wider variety of participants is advised.